A brave new framework for glioma drug development - Hotchkiss, Kelly M.; Karschnia, Philipp; Schreck, Karisa C.; Geurts, Marjolein; Cloughesy, Timothy F.; Huse, Jason; Duke, Elizabeth S.; Lathia, Justin; Ashley, David M.; Nduom, Edjah K.; Long, Georgina; Singh, Kirit; et al. (Lancet Oncology, 2024)
Patients with brain tumours are motivated to participate in clinical trials involving repeat tissue sampling. Normalising the use of neoadjuvant and staged surgical trials necessitates collaboration among patients, regulatory agencies, and researchers. Initial and repetitive tissue sampling plays a crucial role in enhancing our understanding of resistance mechanisms and vulnerabilities in brain tumour therapy. Standardising biopsy techniques and ensuring technical uniformity across institutions are vital for effective interinstitutional collaboration. Although liquid biopsy technologies hold promise, they are not yet ready to replace tissue analysis. Clear communication about the risks and benefits of biopsies is essential, particularly regarding potential postoperative deficits. Changes in mindset and neurosurgical culture are imperative to achieve much needed breakthroughs in the development of new, effective therapies for brain tumours.
CRIS-Team Scopus Importer:2024-10-11